Biblijne argumenty ad absurdum świadectwem prawdziwości wiary chrześcijańskiej - Nawrot, Janusz (Humaniora. Czasopismo Internetowe, 2019)
Argumentum ad absurdum, as a way of thinking or acting which is pointless from the point of view of rationality and predictability of a human’s action, is intentionally planned in order to justify the uniqueness and thus veracity of the existence of something compared to commonly accepted standards of behaviour. The universality of these standards is questioned by introducing factors that go beyond the patterns of commonly accepted standards. In the Bible, there are also absurd situations from the point of view of human predictability which are directly attributed to God. This absurdity of God’s action, in comparison to the rights guiding pagan religions and the rationally accepted human behaviour strengthens the faith in His existence. Going beyond the area of “normalcy” proves in the strongest way that these facts, which are seemingly at variance with logical thinking, are indeed true. These facts are paradoxically a strong and durable foundation of the Christian faith.